Hubungan Antara Self-efficacy Dengan Kepatuhan Pemakaian Insulin Secara Mandiri Pada Pasien DM Di Rumah Sakit Baptis Batu - Diah Fifi Agustina; Feriana Ira Handian; Ach Dafir Firdaus (Jurnal Keperawatan Muhammadiyah, 2020)
ABSTRACTObjective : High level of obedience in using insulin independently in patients with diabetes mellitus is influenced by a person's level of self-efficacy. Methods : This study aims to know the correlation between self-efficacy and obedience of independent insulin use in DM patients at Batu Baptis Hospital. The type of research used is quantitative research using descriptive correlative research design with a cross sectional approach. Sampling used is convenience sampling technique with 125 respondents. Data collection used the DMSES questionnaire (The Diabetes Management Self-efficacy Scale) for the MMAS-8 variable self-efficacy and questionnaire (Morisky Medication Adherence Scale) for compliance variables. The data analysis methods applied the Spearman Rank correlation test. Results : The results of the Spearman Rank test is obtained that p value is 0,000 (p <0.05) and the correlation coefficient value is 0.824. It shows that the strength of the correlation is strong with the direction of the positive correlation. It can be concluded that there is a significant relationship between self-efficacy and obedience of independent use of insulin in DM patients in Batu Baptist Hospital. Conclusion : The higher the self-efficacy in patients is, the higher the patient's compliance with insulin injections. The suggestion of this study it is expected that DM patients who use insulin can be more adherent to undergo treatment with insulin.